Transfer appropriate forgetting: The cue-dependent nature of retrieval-induced forgetting - Jeremy Tree (Journal of Memory and Language, 2004)
Retrieval-induced forgetting is the failure to recall a previously studied word following repeated retrieval of a related item. It has been argued that this is due to retrieval competition between practiced and unpracticed items, which results in inhibition of the non-recalled item, detectable with an independent cue at final test. Three experiments were conducted in which two cues were associated with a target item at encoding. All three studies demonstrated retrieval-induced forgetting when the same retrieval cue was present at practice and test, but not when the second encoding cue was used as an independent probe at final test. These data are not compatible with a general inhibitory account of retrieval-induced forgetting, but support a context-specific account of the phenomenon.